The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/pjfns-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Colour of Strawberry Spread During Storage, Including Effects of Technical Variations

Abstract: The colour of freshly processed strawberry spread changes relatively rapidly from a bright red to a dull red, which then makes its appearance generally less acceptable for consumers. The colours of strawberry spreads following several processing conditions were measured under different storage conditions. Additional sugar and colorant had only slight effects on the colour decay, while exclusion of oxygen and daylight did not affect this process. The only condition that clearly maintained the freshly processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Generally, a decrease in the values of a* was observed, which was probably caused by degradation of anthocyanins. Similar observations were reported by Kadivec et al [2016] with regard to strawberry spreads during storage. Cunja et al [2014], who examined selected rose species and cultivars, found a strong correlation between the parameter a* and total anthocyanin content.…”
Section: Resultssupporting
confidence: 90%
“…Generally, a decrease in the values of a* was observed, which was probably caused by degradation of anthocyanins. Similar observations were reported by Kadivec et al [2016] with regard to strawberry spreads during storage. Cunja et al [2014], who examined selected rose species and cultivars, found a strong correlation between the parameter a* and total anthocyanin content.…”
Section: Resultssupporting
confidence: 90%
“…In this work, L∗ mainly reflects the lightness of the products. Both the TA and sourness parameters are negatively correlated with the tendency for red colour; however, considering that strawberries are a non-climacteric fruit and that replicates were analysed at a similar ripening stage, the tendency to red colour in this study was probably mainly linked to varietal characteristics [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of colour in horticultural products, which usually supersedes the importance of either flavour or texture [ 21 ], colorimetric analyses were performed with a CR-400 colorimeter (Konica Minolta, Tokyo, Japan) in the equatorial zones of the most and least colourful sides of twenty fruits for each replicate. The L∗, a∗, and b∗ values were recorded with Konica Minolta software (Spectra Magic NX).…”
Section: Methodsmentioning
confidence: 99%
“…The colour of freshly strawberry normally changes from a bright red to a dull red colour throughout the storage time, which then makes its appearance generally less acceptable for customer [23]. Based on the observation, the strawberry treated with 1.0 kJ/m2 of dosage succeed to maintain the red colour of strawberry surface throughout the storage time, with showing more surface reddening than the control 0kJ/m2 of dosage.…”
Section: Treatments and Postharvest Analysismentioning
confidence: 97%